CFD modeling of combustion of sugarcane bagasse in an industrial boiler (2017)
In this study, a CFD model is developed to evaluate the performance of an industrial boiler furnace running on sugarcane bagasse. The model was developed in the commercial software ANSYS FLUENT and includes user-defined functions programmed in C language defining devolatilization phenomenon as well as combustion on the grate. The simulation results suggests that devolatilization is the dominant phenomenon through the largest portion of the particle trajectory, and hence an important factor in predicting the thermal fields. On the other hand, the char is burned on the grate or entrained through the furnace outlet. The general efficiency indicators obtained from particle combustion description could then allow us to compare different design and operational alternatives